A PROBABILITY ANALYSIS OF CONSTRUCTION PROJECT SCHEDULE USING RISK MANAGEMENT TOOL - Agarwal, A L; Mahajan, D A (MATTER: International Journal of Science and Technology, 2017)
The construction industry tumbled along with the other industry/sectors during the recent economic crash. Construction business could not regain thereafter and is still passing through a slowdown phase, resulting in time and cost overrun of many real estate as well as infrastructure projects. There are many theories, tool and techniques with software packages available in the market to analyze construction schedule. This study focuses on the construction project schedule and uncertainties associated with construction activities. The infrastructure construction project has been considered for the analysis of uncertainty on project activities affecting project duration and analysis is done using @RISK software. Different simulation results arising from three probability distribution functions are compiled. This study helps construction project managers to plan and prepare more realistic schedules for construction projects and document probable project completion date in the contract to avoid compensations or claims arising due to missing the planned schedule.